Examining the Impact of School Type on Physical Activity Participation in High School Students. Issue 3 (3rd July 2019) - Sweeney, Thomas P.; Gray, Joey
ABSTRACT: Changing education philosophies and technological advancement have altered the way educational content can be delivered to students. One format growing in popularity is virtual institutions which allow students to complete their secondary education completely online. While the format has been in existence for two decades, little information has been presented regarding how the shift from a traditional brick and mortar environment to a virtual one impacts the physical activity of the students. The purpose of this study is to determine the effect of school type on physical activity participation. One hundred fifteen high school age students attending brick and mortar and virtual institutions completed a survey regarding their physical activity participation. Results indicate students who attend virtual institutions are more likely to be physically active than their brick and mortar counterparts.